A High Fat Diet during Adolescence in Male Rats Negatively Programs Reproductive and Metabolic Function Which Is Partially Ameliorated by Exercise - Ibáñez, Carlos A.; Erthal, Rafaela P.; Ogo, Fernanda M.; Peres, Maria N. C.; Vieira, Henrique R.; Conejo, Camila; Tófolo, Laize P.; Francisco, Flávio A.; da Silva Silveira, Sandra; Malta, Ananda; Pavanello, Audrei; Martins, Isabela P.; et al. (Frontiers in Physiology, 2017)
An interaction between obesity, impaired glucose metabolism and sperm function in adults has been observed but it is not known whether exposure to a diet high in fat during the peri-pubertal period can have longstanding programmed effects on reproductive function and gonadal structure. This study examined metabolic and reproductive function in obese rats programmed by exposure to a high fat (HF) diet during adolescence. The effect of physical training (Ex) in ameliorating this phenotype was also assessed. Thirty-day-old male Wistar rats were fed a HF diet (35% lard w/w) for 30 days then subsequently fed a normal fat diet (NF) for a 40-day recovery period. Control animals were fed a NF diet throughout life. At 70 days of life, animals started a low frequency moderate exercise training that lasted 30 days. Control animals remained sedentary (Se). At 100 days of life, biometric, metabolic and reproductive parameters were evaluated. Animals exposed to HF diet showed greater body weight, glucose intolerance, increased fat tissue deposition, reduced VO2max and reduced energy expenditure. Consumption of the HF diet led to an increase in the number of abnormal seminiferous tubule and a reduction in seminiferous epithelium height and seminiferous tubular diameter, which was reversed by moderate exercise. Compared with the NF-Se group, a high fat diet decreased the number of seminiferous tubules in stages VII-VIII and the NF-Ex group showed an increase in stages XI-XIII. HF-Se and NF-Ex animals showed a decreased number of spermatozoa in the cauda epididymis compared with animals from the NF-Se group. Animals exposed to both treatments (HF and Ex) were similar to all the other groups, thus these alterations induced by HF or Ex alone were partially prevented. Physical training reduced fat pad deposition and restored altered reproductive parameters. HF diet consumption during the peri-pubertal period induces long-term changes on metabolism and the reproductive system, but moderate and low frequency physical training is able to recover adipose tissue deposition and reproductive system alterations induced by high fat diet. This study highlights the importance of a balanced diet and continued physical activity during adolescence, with regard to metabolic and reproductive health.